PERKEMBANGAN FIKTIF NEGATIF DAN TINDAKAN FAKTUAL BERSIFAT OMISI DI PERADILAN TATA USAHA NEGARA - Aju Putrijanti; Dani Habibi; Anggita Doramia Lumbanraja (Program Magister Hukum Universitas Lambung Mangkurat, 2026)
This research focus on the development of fictitious negative and factual act omission after Supreme Court Regulation Number 2 of 2024 issued. The principle lex posteriori derogat legi priori was implemented against Article Number 3 of Law Number 5 of 1986 of Administrative Court. It was caused by the stipulation of Article Number 53 of Law Number 30 of 2014 of Government Administration, stated that the Administrative Court has authority to examine fictitious positive application, but then it was eliminated by Law Number 11 of 2020 of Job Creation. This elimination caused legal gap and legal uncertainty about the mechanism to get government decree and access to justice. People tried to used mechanism of factual act omission lawsuit, to get justice, because, first, there is no certain regulation which gives authority to Administrative Court to examine fictitious positive application, second, to give justice and legal certainty. The aims of this research are to get to know the development of fictitious negative and factual act omission lawsuit and the regulation refer to fictitious negative and factual act omission lawsuit as access to justice. This research used a doctrinal method and statute approach, conceptual approach and comparative approach to analysis and answer the legal problems. Research results shows fictitious negative lawsuit mechanism can be used to get access to justice, because, there is no cancellation of this regulation, and to give legal certainty and justice to whomsoever might needed. Government should make a new regulation according to Administrative Court system, which resolve the legal problems and legal certainty, and to fulfilled access to justice.